The Effects of Tobacco Use on Oral Health and the Role of Oral Healthcare Providers in the Cessation of the Habit - Dr. Manisha Pathak, Dr Abhinav Bhargava ,Dr. Madhvika Patidar ,Ganganna Kokila, Dr Abhishek Ranjan Pati , Dr Rashmita Nayak (South Eastern European Journal of Public Health, 2025)
Tobacco use, both in smoking and smokeless forms, is a major risk factor for various oral health issues, including periodontal disease, oral cancer, and tooth loss. While awareness of these risks is widespread, tobacco cessation remains a persistent challenge. This study aims to assess the impact of tobacco use on oral health and evaluate the role of oral healthcare providers in promoting cessation. A questionnaire-based survey was conducted with 20 participants to explore their awareness, attitudes, and perceptions regarding tobacco use and the involvement of dental professionals in tobacco cessation. The findings emphasize the need for enhanced communication, guidance, and support from oral healthcare providers to effectively address tobacco-related oral health concerns.